Pengaruh Indeks Pembangunan Gender dan Indeks Pemberdayaan Gender Terhadap Pertumbuhan Ekonomi di Provinsi Kalimantan Selatan Tahun 2018-2022 - Norvita, Haniah; Fahrati, Eny (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2025)
The purpose of this study is to investigate the effect of Gender Development Index and Gender Empowerment Index on economic growth measured through Gross Regional Domestic Product with secondary data. The analysis method used is panel data regression by applying fixed effect model. The results showed that: (1) Gender Development Index and Gender Empowerment Index affect the economic growth of South Kalimantan Province in 2018-2022 simultaneously and partially; (2) Gender Development Index is the most dominant influence.